A mulher no romance machadiano - Vieira, Andressa dos Santos (2023)
The female characters in Machado de Assis' work have aroused fascination in many of his readers over several generations, especially because of the singular way their profiles were constructed in his writings. Facing the growing, and urgent, need to place women in a prominent position, selected for analysis some female characters that compose the novels Resurrection (1872), The Hand and the Glove (1874), Helena (1876), Iaiá Garcia (1878), The Posthumous Memoirs of Brás Cubas (1881), Quincas Borba (1891), Dom Casmurro (1899), Esau and Jacob (1904) and Counselor Ayres' Memorial (1908), seeking to highlight both the characters who occupy a position of protagonism in the plots and those who occupy a secondary position and that, due to this, ended up neglected or put aside by a critique made up mostly of men. The analysis aims to identify how patriarchy, so rooted in 19th-century Brazilian society, especially within the wealthier classes, interferes in the way of life of these women, of distinct ages and social positions, through the power relations that will dictate the rules about the family, social and loving relationships maintained by them and that cross these narratives as a theme while shedding light over the scenario which the writer used to live, and on his vision of the female universe, transported to the literary texts produced by him in the course of almost four decades of intense novelistic production.